KONSEP INTEGRASI TASAMUH QUR’ANI DALAM PENDIDIKAN MODERASI BERAGAMA - Luqyana Azmiya Putri; Doli Witro (Balai Diklat Keagamaan Medan, 2022)
Today, Muslims are faced with two challenges that will be faced in understanding and implementing Islamic religious texts. First, the existence of a relaxed tendency in religion is a challenge for Muslims where this tendency triggers a person to become religious by following their passions and underestimating religious teachings. Second, in addition to the tendency to look beyond the inside, Muslims are also faced with the challenge of the tendency to overestimate and exceed limits in understanding religious texts. The Indonesian Ministry of Religion is aggressively campaigning for religious moderation, even in the realm of education. One indicator of religious moderation is tolerance. However, the current reality shows that there is a tendency of tolerance by going beyond limits, thinking too openly to get out of the signs of Islamic law. Therefore, this article will discuss the concept of integration of tasamuh based on Al-Quran to be applied in religious moderation education. The research method used is qualitative research with a library research approach. The results show that one of the concepts of integrating tasāmuh (tolerant) values is through educational institutions. The concept of tasamuh qurani makes Al-Quran the main basis where it is stated that brotherhood between fellow humans is good, namely by always being patient with the beliefs of other religions. Even though their teachings are false according to Islam, Allah still does not encourage Muslims to criticize and hurt people of other religions.